Gig economy platforms: Boon or Bane? - Schwellnus, Cyrille (OECD Publishing, 2019)
The rapid emergence of gig economy platforms that use digital technologies to intermediate labour on a per-task basis has triggered an intense policy debate about the economic and social implications. This paper takes stock of the emerging evidence. The results suggest that gig economy platforms' size remains modest (1-3 per cent of overall employment). Their growth has been most pronounced in a small number of services industries with high shares of own-account workers, suggesting that thus far they have been a substitute for traditional self-employment rather than dependent employment. New evidence provided in this paper is consistent with positive effects of platform growth on overall employment and small negative or insignificant effects on dependent employment and wages. While most empirical studies suggest that platforms are more efficient in matching workers to clients, reductions in barriers to work could offset such productivity-enhancing effects by creating employment opportunities for low-productivity workers. Fully reaping the potential benefits from gig economy platforms while protecting workers and consumers requires adapting existing policy settings in product and labour markets and applying them to traditional businesses and platforms on an equal footing
Keywords: Economics